Sleep Misperception and Associated Factors in Patients With Anxiety-Related Disorders and Complaint of Insomnia: A Retrospective Study - Liang, Yingjie; Zhao, Xu; Zhang, Changyong; Liu, Guangya; Lu, Baili; Han, Li; Tong, Fang; Luo, Xinyu; Hu, Chuang; Liu, Hui (Frontiers in Neurology, 2022)
Purpose: Data on sleep parameters by polysomnography (PSG) in patients with anxiety-related disorders are limited. Although the disturbance and risk factors of sleep misperception have been implicated in psychopathology, its role in anxiety-related disorders remains unclear. This retrospective study aimed to explore the characteristics and sleep parameters in patients with anxiety-related disorders and different sleep perception types, and to explore the associated factors for sleep misperception. Methods: Patients with anxiety-related disorders who had complaint of insomnia for more than 3 months were collected at Wuhan Mental Health Center between December 2019 and July 2021. Patients underwent two-night PSG monitoring and completed a self-reported sleep questionnaire, and behaviors were assessed using 30-item Nurses’ Observation Scale for Inpatient Evaluation (NOSIE-30). Patients were divided into normal sleep perception (NSP), positive sleep perception abnormality (PSPA; overestimation of total sleep time [TST] >60 min), and negative sleep perception abnormality (NSPA; underestimation of TST >60 min) groups. PSG indicators and NOSIE-30 scores were compared among groups using the one-way analysis of variance and Kruskal-Wallis test. Multiple linear regression analysis was performed to determine the associated factors for misperception index Results: The subjective and objective TST were 5.5±1.9 h and 6.4±1.7 h in 305 patients, respectively. Sixty-nine (22.6%) had PSPA, 80 (26.2%) had NSP, and 156 (51.1%) had NSPA. Subjective TST and objective sleep parameters were significantly different among groups. No statistical differences in NOSIE-30 subscale and total scores were observed among groups. Sex, REM/TST (%), sleep efficiency, number of awakenings , N2/TST (%), REM spontaneous arousal times , sleep latency , diagnosis, social competence and manifest psychosis were associated with sleep misperception. Conclusion: Sleep misperception is common in patients with anxiety-related disorders. Various sleep perception types have different PSG profiles, but similar personal and social behaviors. These data may be helpful to conduct personalized treatment.